A randomized, open-label and prospective study to compare the efficacy and safety of synbiotics and rosuvastatin along with concomitant ursodeoxycholic acid in non-alcoholic fatty liver disease in North India - Arora, Malika; Randhawa, Gurpreet Kaur; Grover, Inderpal Singh; Chander, Rakesh; Ohri, Poonam (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Non-alcoholic fatty liver disease (NAFLD) is a chronic liver disorder without significant alcohol consumption with a global prevalence of 32%. It is strongly associated with dyslipidemia, obesity, insulin resistance and gut dysbiosis with no current USFDA approved pharmacotherapy. Thus, this study aims to compare the efficacy and safety of Synbiotics and Rosuvastatin along with concomitant Ursodeoxycholic Acid (UDCA), in treatment of NAFLD. Methods: An interventional, randomized, open-label, prospective and parallel study of 12 weeks with patients randomly divided into two groups- A and B of thirty each. Group A was prescribed Synbiotics (Velgut) 5 billion CFUs BD and Group B was prescribed Rosuvastatin 20 mg OD along with UDCA 300mg BD in both the groups. Patients were followed up every 15 days and mainly assessed on hepatic profile, ultrasound grading, FibroScan, fibrosis indices and lipid profile along with safety profile and compliance. Results: On comparison, Group A showed significant improvement in hepatic parameters (p<0.001) whereas Group B showed better improvement in lipid profile (p<0.001). In case of ultrasonography for hepatic steatosis and assessment of liver stiffness by FibroScan, both Group A and B showed comparable improvement over 90 days (p=0.143 and p=0.722, respectively) with no worsening of any grades. Both groups performed similarly in terms of safety (p>0.05) and patients showed good compliance (p>0.05). Conclusion: Combination of Synbiotics and UDCA (Group A) seems to be more efficacious than Rosuvastatin and UDCA (Group B) in North-Indian NAFLD patients over a period of 3 months. Further extensive research with more sample size and studies with longer duration are needed to validate the role of these combination therapies in NAFLD.